New Technologies for Climbing Robots Adhesion to Surfaces - Silva, Manuel F. (2019)
The interest in the development of climbing robots is growing steadily. The main motivations are to increase the operation e ciency, by eliminating the costly assembly of sca olding, or to protect human health and safety in hazardous tasks. Climbing robots have already been developed for applications ranging from cleaning to inspection of constructions di cult to reach. These robots should be capable of travelling over di erent types of surfaces, with di erent inclinations, such as oors, walls, ceilings, and to walk between such surfaces. Furthermore, they should be able of adapting and recon guring for di erent environment conditions and to be self-contained. Regarding the adhesion to the surface, the robots should be able to produce a secure gripping force using a light-weight mechanism. This paper presents a survey of di erent technologies proposed and adopted for climbing robots adhesion to surfaces, focusing on the new technologies that are recently being developed to ful ll these objectives.